Chemical Composition and Antibacterial Activity of the Essential Oil of Kauri Pine [ Agathis robusta (C. Moore ex F. Muell.) F.M. Bailey] from India. (3rd July 2016) - Verma, Ram S.; Padalia, Rajendra C.; Goswami, Prakash; Verma, Sajendra K.; Chauhan, Amit; Darokar, Mahendra P.
Abstract : Agathis robusta (C. Moore ex F. Muell.) F.M. Bailey, commonly known as Queensland Kauri or smooth-barked Kauri, is a coniferous tree in the family Araucariaceae. This study aimed to investigate the chemical composition and antibacterial activity of the essential oil of A. robusta from India. The hydrodistilled resin and leaf essential oils were analyzed using GC-FID and GC-MS. Altogether, 34 constituents (forming 98.2% of the resin oil) and 43 constituents (forming 91.2% of the leaf oil composition) were identified. Major constituents of the resin oil were isobornyl acetate (37.9%), limonene (12.3%), bornyl acetate (7.4%), and myrtenol (5.8%), while the leaf oil contained β-selinene (18.1%), rimuene (14.2%), caryophyllene oxide (11.5%), spathulenol (10.5%), α-selinene (9.8%), and γ-muurolene (5.8%) as main constituents. The resin essential oil showed minimum inhibitory concentration (MIC) in the range of 250–500 μg/mL and minimum bactericidal concentration (MBC) in the range of 500 to >1000 μg/mL against pathogenic strains of eight bacteria.